ANALISIS PENAWARAN EKSPOR KARET ALAM INDONESIA KE NEGARA CINA - Tanti Novianti; Ella Hapsari Hendratno (School of Business, Bogor Agricultural University (SB-IPB), 2008)
The purposes of this research are to identified export supply growth of China’s natural rubber, analyzed factors of influenced export supply of Indonesian natural rubber to China, and also analyze the export growth strategic of Indonesian natural rubber. The description method is used to identified marketgrowth in Indonesian natural rubber. The second purposes answered by multiple linier regression with Ordinary Least Square (OLS). Export growth stategic have been analyzed by SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). Based on The OLS result, variabel which make infuence for export supply of Indonesian natural rubber in China export price of Indonesian natural rubber to Chinain previous years, The world rice of synthetic rubber, GDP of China, lag export volume of Indonesian natural rubber to China. The growth strategic for increase Indonesian market in China are increase Indonesian natural rubber productivity. Increased productivity will come true by renew the planting ofrubber and to aplicating relationship between farmers and government plantage.